Preparation method of low-dielectric polyimide heat-conducting film
The modified boron nitride polyimide film is formed by ultrasonic-assisted peeling and in-situ reaction, which solves the problems of insufficient thermal conductivity and high dielectric constant, and achieves the matching of high thermal conductivity and low dielectric properties , suitable for electronic packaging materials in the field of 5G communications.
Patent Information
- Application Number
- CN202310694400.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively prepare polyimide thermal conductivity films with high thermal conductivity and low dielectric properties. Especially in the field of 5G communications, traditional methods have problems such as insufficient thermal conductivity and high dielectric constant, and hexagonal boron nitride The batch preparation process of nanosheets is complex and inefficient.
Hexagonal boron nitride nanosheets were prepared by ultrasonic assisted organic solvents, and in situ reacted with dianhydride monomers in the polyimide matrix to form modified boron nitride polyimide Thin film improves the matching of thermal conductivity and dielectric properties.
It achieves a significant improvement in thermal conductivity while maintaining a low dielectric constant. The process is simple and suitable for batch preparation, avoiding the problems of crystal defects and interface thermal resistance.
Smart Images

Figure HSA0000297060630000011 
Figure HSA0000297060630000012 
Figure HSA0000297060630000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermally conductive composite materials, and in particular to a method for preparing a low-dielectric polyimide thermally conductive film. Background Art
[0002] In recent years, with the rapid development of microelectronics technology, electronic devices are rapidly developing in the direction of miniaturization, high speed and multi-function. A large number of electronic components are concentrated in a very small space. Timely heat dissipation is of great significance to improving the service life and reliability of electronic devices. Therefore, electronic packaging materials with high heat dissipation efficiency are highly anticipated. However, in addition to high thermal conductivity, in practical electronic applications, especially 5G in the field of communications, because 5G has a faster transmission speed and poor transmission signal strength, these materials are required to have a small dielectric constant and dielectric loss. However, there are currently few research reports on materials with high thermal conductivity and low dielectric properties, so it is still technically challenging to prepare thermally conductive polymer composites with lower dielectric properties using a simple process.
[0003] Polyimide (PI) is a well-known material with excellent dielectric properties, low thermal expansion, high strength and thermal stability, and is therefore widely used in packaging materials, circuit boards and interlayer dielectric materials. Polyimide films also have good flexibility and excellent processability. However, similar to most polymers, traditional PI has the disadvantage of poor thermal conductivity. When used as electronic packaging and electronic devices, the thermal conductivity coefficient (0.1-0.2W / m K) cannot meet the heat dissipation requirements of high power, high density and high integration of microelectronic packaging materials, which seriously affects the performance and service life of the device. In order to improve the thermal conductivity of PI, extensive research has focused on introducing thermally conductive fillers into polymer matrices, such as carbon nanotubes, graphene oxide, ceramic oxides and nitrides. Among the available fillers, hexagonal boron nitride is one of the outstanding candidates for the preparation of high thermal conductivity composite materials due to its excellent electrical insulation, high thermal stability and low dielectric constant. However, there is still no mature process for the batch preparation and functionalization of hexagonal boron nitride nanosheets. The most common method is to prepare nanosheets by chemical vapor deposition, mechanical exfoliation, liquid ultrasonic exfoliation, etc., and then further modify and functionalize them after purification. These preparation methods have problems such as poor product crystal form, complex experimental process, high consumption and many impurities, easy to cause defects in nanosheets, and low yield. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a one-step modification method for boron nitride, which grafts a small amount of alkyl groups on the boundary of boron nitride to ensure the integrity of its crystal structure, which has great reference value for batch preparation of few-layer boron nitride nanosheets. A method for preparing a low-dielectric polyimide thermal conductive film, after the hexagonal boron nitride is modified, it can not only improve the compatibility of hexagonal boron nitride with polyimide, but also promote its uniform dispersion in the polyimide matrix, thereby obtaining a low-dielectric polyimide thermal conductive film.
[0005] To this end, the technical solution of the present invention is as follows:
[0006] 1) Exfoliation and modification of boron nitride: commercial boron nitride powder is placed in a predetermined proportion of primary alcohol solvent, and the boron nitride is exfoliated and modified by using an ultrasonic-assisted organic solvent. After the ultrasonic exfoliation is completed, the obtained boron nitride suspension is centrifuged to remove the unexfoliated multilayer boron nitride to prepare a modified boron nitride nanosheet suspension, which is then filtered and dried to obtain the modified boron nitride nanosheet.
[0007] Furthermore, the primary alcohol solvent may be propanol, butanol, pentanol or hexanol.
[0008] Furthermore, the ultrasonic treatment time is 4 to 10 hours, and the ultrasonic temperature is 10 to 30°C.
[0009] Furthermore, the speed of the centrifugal treatment is 1000-3000 r / min, and the time is 10-30 min.
[0010] Furthermore, the filtering device is a sand core suction filtration, and the filter membrane is a polytetrafluoroethylene organic membrane.
[0011] Furthermore, the drying temperature is 60 to 140° C., and the drying time is 4 to 10 hours.
[0012] 2) preparing a polyamic acid solution: in an inert atmosphere, in a three-necked flask equipped with a mechanical stirrer and a vent tube, first add a diamine monomer into an organic solvent until it is completely dissolved, then add a dianhydride monomer in batches while maintaining high-speed stirring and stir evenly, and react for a certain period of time in an ice-water bath to obtain a polyamic acid solution.
[0013] Furthermore, the organic solvent may be one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N,N-dimethylethanolamine (DMEA).
[0014] Furthermore, the inert atmosphere can be a mixture of one or more of nitrogen and argon, wherein the gas flow rate is 50 to 100 mL / min.
[0015] Furthermore, the diamine monomer may be one or a mixture of 4,4'-diaminodiphenyl ether (ODA), 4,4'-methylenedianiline (MDA), metaphenylenediamine (MPD), ethylenediamine (EDA), hexamethylenediamine (HDA) or 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFDB).
[0016] Furthermore, the dianhydride monomer may be one or a mixture of pyromellitic dianhydride (PMDA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), ethylenediaminetetraacetic dianhydride (EDTA), and 4,4'-oxydiphthalic acid (ODTA).
[0017] Furthermore, the dianhydride monomer is added in 4 batches, with an interval of 10-20 minutes between each batch. After each added dianhydride monomer is completely dissolved, the next batch of dianhydride monomer is added, and the amount added each time is half of the previous amount.
[0018] Furthermore, the mechanical stirring rate is 200-400 r / min, and the reaction time is 5-12 h.
[0019] Furthermore, the molar ratio of the diamine reactive monomer to the dianhydride reactive monomer is 1:1 to 1.1.
[0020] 3) taking a certain proportion of the modified boron nitride nanosheets prepared in step 1) and ultrasonically dispersing them in an organic solvent to obtain a suspension, and mixing them evenly with the polyamic acid solution prepared in step 2) under ultrasonic conditions, coating a film of a certain thickness on a smooth glass plate using a scraper, and finally achieving imidization in a vacuum high temperature environment to convert them into a modified boron nitride polyimide film.
[0021] Furthermore, the mass percentage of the modified boron nitride nanosheets is 5-20wt%.
[0022] Furthermore, the organic solvent may be one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N,N-dimethylethanolamine (DMEA).
[0023] Furthermore, the thickness of the membrane may be between 200 and 500 μm.
[0024] Furthermore, the high temperature includes the following temperature stages, wherein the first temperature stage is 80-100°C, and the insulation time is 1-2h; the second temperature stage is 100-150°C, and the insulation time is 1-2h; the third temperature stage is 150-200°C, and the insulation time is 1-2h; the fourth temperature stage is 200-300°C, and the insulation time is 1-2h; the modified polyamic acid undergoes the above temperature stages in sequence to complete imidization.
[0025] The present invention has the following advantages and beneficial effects:
[0026] 1. In the present invention, hexagonal boron nitride nanosheets are prepared by ultrasonic-assisted organic solvent exfoliation, and the functional modification of the nanosheets is achieved in the solution. The preparation method is simple in process, and simultaneous exfoliation and modification are achieved in one step, which has great reference value for the batch preparation of few-layer boron nitride nanosheets.
[0027] 2. In the present invention, the modification method will not increase the interface thermal resistance due to the addition of another interface material, nor will it affect the thermal conductivity of boron nitride itself due to crystal defects caused by basic covalent bonds.
[0028] 3. In the present invention, modified boron nitride is introduced into the polyimide matrix, and then the composite film is prepared in situ, which enhances the compatibility between the filler and the polymer. The thermal conductivity (λ) of the obtained composite material is significantly improved, and the dielectric constant (ε) is relatively low. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Fourier transform infrared spectra of hexagonal boron nitride before and after exfoliation modification;
[0030] Figure 2 It is the Fourier transform infrared spectrum of polyamic acid, polyimide and its composite thermal conductive film;
[0031] Figure 3 This is a scanning electron microscope photograph of the modified boron nitride polyimide thermal conductive film obtained in Example 1;
[0032] Figure 4 This is a scanning electron microscope image of the pure polyimide film obtained in Comparative Example 1; DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0034] Example 1
[0035] 1) Exfoliation of modified boron nitride: Using n-hexanol as the raw material, alkyl boron nitride nanosheets were prepared by ultrasonic-assisted alcoholysis. 1 g of hexagonal boron nitride was added to 500 mL of n-hexanol, stirred vigorously until the solution was uniform, and the mixture was ultrasonically crushed for 10 h using an ultrasonic cleaner. Then, vigorous mechanical stirring and ultrasonic treatment were performed to obtain a redispersed solution, which was centrifuged at 2500 rpm for 30 min. The supernatant was filtered with a PTFE membrane filter (diameter 50 mm, pore size 0.22 μm). The product was washed alternately with ethanol and deionized water for 3 times to remove impurities, and then dried at 60 ° C for 7 h and 140 ° C for 3 h in a vacuum oven to obtain modified boron nitride nanosheets.
[0036] 2) Preparation of polyamic acid solution: A series of modified boron nitride / polyamic acid solutions were synthesized by in-situ polymerization. We put 3.2 g of 2,2'-bis(trifluoromethyl)diaminobiphenyl into a three-necked flask containing N,N-dimethylacetamide and stirred it under nitrogen purge at 0°C until 2,2'-bis(trifluoromethyl)diaminobiphenyl was completely dissolved. 4,4'-(hexafluoroisopropyl)diphthalic anhydride was added in 4 batches (the molar ratio of diamine to dianhydride monomer was 1:1.01). Each batch was added to the above system every 20 minutes and stirred for 12 hours to form a uniform viscous polyamic acid solution.
[0037] 3) Take 5wt% of the modified boron nitride nanosheets prepared in step 1) and ultrasonically disperse them in N,N-dimethylacetamide to obtain a suspension, and mix them evenly with the polyamic acid solution prepared in step 2) under ultrasonic conditions. Spread the obtained mixed solution on a clean glass plate with a thickness of 500μm, and then dry it at 80°C for 1 hour to evaporate the residual solvent. The samples were imidized in a high-temperature vacuum oven at 150, 200, and 300°C for 1 hour. Finally, the composite film was cooled to room temperature, soaked in distilled water and peeled off from the glass substrate to prepare a modified boron nitride / polyimide thermal conductive film.
[0038] like Figure 1 As shown in the figure, the hexagonal boron nitride before modification only has -1 Two strong characteristic peaks appear at 2849cm -1 and 2920cm -1 Two characteristic peaks appear at , which are attributed to the CH chains of methylene and methyl respectively.
[0039] like Figure 2 As shown, polyamic acid is at 1657cm -1 、1710cm -1 and 3500cm -1 The characteristic absorption peak appears near 1780 cmm, but the above characteristic peak disappears in polyimide. -1 、1720cm -1 and 1370cmm -1 The characteristic peak near 750cm is attributed to the absorption peak of the imide ring, which is similar to the polymer. -1 The characteristic peak corresponding to BN was found at
[0040] Implementation effect: The thermal conductivity of the prepared modified boron nitride polyimide dielectric thermal conductive composite material is 2.24W / m K and ε is 2.71. The scanning electron microscope photo of the modified boron nitride polyimide thermal conductive film is shown in the figure. Figure 3 shown.
[0041] Comparative Example 1
[0042] The difference between this comparative example and Example 1 is that step 1) is not performed, no filler is added in step 3), and the polyamic acid solution obtained in step 2) is directly coated on the glass plate.
[0043] Implementation effect: The λ of the prepared polyimide film is 0.44W / m K and ε is 2.58. The scanning electron microscope image of the pure polyimide film is as follows Figure 4 shown.
[0044] Comparative Example 2
[0045] The difference between this comparative example and Example 1 is that in step 1), the hexagonal boron nitride is not modified, and in step 3), the amount of hexagonal boron nitride added is 5 wt %.
[0046] Implementation effect: The prepared modified boron nitride polyimide dielectric thermal conductive composite material has a lambda of 1.54 W / m K and an ε of 2.79.
[0047] Example 2
[0048] The difference between this embodiment and embodiment 1 is that the amount of modified boron nitride added in step 3) is 10 wt %.
[0049] Implementation effect: The prepared modified boron nitride polyimide dielectric thermal conductive composite material has a lambda of 2.96 W / m K and an ε of 2.85.
[0050] Example 3
[0051] The difference between this embodiment and embodiment 1 is that the amount of modified boron nitride added in step 3) is 15 wt %.
[0052] Implementation effect: The prepared modified boron nitride polyimide dielectric thermal conductive composite material has a lambda of 4.13 W / m K and an ε of 2.91.
[0053] Example 4
[0054] The difference between this embodiment and embodiment 1 is that the amount of modified boron nitride added in step 3) is 20 wt %.
[0055] Implementation effect: The prepared modified boron nitride polyimide dielectric thermal conductive composite material has a lambda of 6.21 W / m K and an ε of 3.23.
[0056] Comparative Example 3
[0057] The difference between this comparative example and Example 1 is that in step 1), the hexagonal boron nitride is not modified, and in step 3), the amount of hexagonal boron nitride added is 10 wt %.
[0058] Implementation effect: The prepared boron nitride polyimide dielectric thermal conductive composite material has a lambda of 2.35 W / m K and an ε of 3.34.
[0059] Comparative Example 4
[0060] The difference between this comparative example and Example 1 is that in step 1), the hexagonal boron nitride is not modified, and in step 3), the amount of hexagonal boron nitride added is 15 wt %.
[0061] Implementation effect: The prepared boron nitride polyimide dielectric thermal conductive composite material has a lambda of 2.78 W / m K and an ε of 3.7.
[0062] Comparative Example 5
[0063] The difference between this comparative example and Example 1 is that in step 1), the hexagonal boron nitride is not modified, and in step 3), the amount of hexagonal boron nitride added is 20 wt%.
[0064] Implementation effect: The prepared boron nitride polyimide dielectric thermal conductive composite material has a lambda of 3.7 W / m K and an ε of 4.58.
[0065] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned manner. As long as various improvements are made using the method concept and technical solution of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a low dielectric polyimide thermally conductive film, characterized in that The steps include: 1) Exfoliation and modification of boron nitride: placing commercial boron nitride powder in a primary alcohol solvent of a predetermined proportion, exfoliating and modifying the boron nitride with the aid of an organic solvent using ultrasound, and after the ultrasonic exfoliation is completed, centrifuging the obtained boron nitride suspension to remove the unexfoliated multilayer boron nitride, thereby preparing a modified boron nitride nanosheet suspension, which is then filtered and dried to obtain the modified boron nitride nanosheet; 2) preparing a polyamic acid solution: introducing an inert atmosphere such as nitrogen or argon at a gas flow rate of 50 to 100 mL / min, first adding a diamine monomer to an organic solvent in a three-necked flask equipped with a mechanical stirrer and a vent pipe until the diamine monomer is completely dissolved, and then adding a dianhydride monomer in 4 batches with a stirring speed of 200 to 400 r / min, stirring each batch for 10 to 20 minutes, and reacting in an ice-water bath for 5 to 12 hours to prepare a polyamic acid solution; 3) 5-20wt% of the modified boron nitride nanosheets prepared in step 1) are ultrasonically dispersed in the organic solvent in step 2) to obtain a suspension, and the suspension is uniformly mixed with the polyamic acid solution prepared in step 2) under ultrasonic conditions, and a film of 200-500μm is coated on a smooth glass plate using a scraper, and finally imidization is carried out in a vacuum high temperature environment to convert it into a modified boron nitride polyimide film.
2. The method for preparing a low dielectric polyimide thermally conductive film according to claim 1, characterized in that: The primary alcohol solvent in step 1) can be propanol, butanol, pentanol or hexanol.
3. The method for preparing a low dielectric polyimide thermal conductive film according to claim 1, characterized in that: In step 1), the ultrasonic treatment time is 4 to 10 hours, the ultrasonic temperature is 10 to 30° C.; the centrifugal treatment speed is 1000 to 3000 r / min, and the time is 10 to 30 minutes; the filtration device is a sand core filtration, and the filter membrane is a polytetrafluoroethylene organic membrane; the drying temperature is 60 to 140° C., and the time is 4 to 10 hours.
4. The method for preparing a low dielectric polyimide thermal conductive film according to claim 1, characterized in that: The diamine monomer in step 2) can be one or a mixture of 4,4'-diaminodiphenyl ether (ODA), 4,4'-methylenedianiline (MDA), metaphenylenediamine (MPD), ethylenediamine (EDA), hexamethylenediamine (HDA) or 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFDB).
5. The method for preparing a low dielectric polyimide thermal conductive film according to claim 1, characterized in that: The dianhydride monomer in step 2) can be one or a mixture of pyromellitic dianhydride (PMDA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), ethylenediaminetetraacetic dianhydride (EDTA), and 4,4'-oxydiphthalic acid (ODTA).
6. The method for preparing a low dielectric polyimide thermal conductive film according to claim 1, characterized in that: In step 2), the molar ratio of the diamine reaction monomer to the dianhydride reaction monomer is 1:1 to 1.
1.
7. The method for preparing a low dielectric polyimide thermal conductive film according to claim 1, characterized in that: The organic solvent in step 2) can be one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N,N-dimethylethanolamine (DMEA).
8. The method for preparing a low dielectric polyimide thermal conductive film according to claim 1, characterized in that: The high temperature in step 3) includes the following temperature stages, wherein the first temperature stage is 80-100°C, and the insulation time is 1-2h; the second temperature stage is 100-150°C, and the insulation time is 1-2h; the third temperature stage is 150-200°C, and the insulation time is 1-2h; the fourth temperature stage is 200-300°C, and the insulation time is 1-2h.
Citation Information
Cited By
Preparation method and application of electric breakdown-resistant corona-resistant polyimide film
CN122011458A
Preparation method and application of a polyimide film resistant to electric breakdown and corona
CN122011458B
